Dimensionamiento e implementación de una máquina CNC de corte por láser para optimizar la calidad de trabajos en acrílico de hasta 5 mm de espesor - Cruz Carrillo, Néstor Xavier (2017)
The problem focuses on the processes of acrylic machining applied in the "Licero" workshops. These are limited to cuts and engravings limited to circular sawing and milling cutters. The work done with these tools limits the productive offer of the workshop with basic designs with straight geometries and basic curves. A new cutting and engraving system is executed using CNC (Computer Numerical Control) laser cutting equipment for acrylic work up to 5 mm thick. In addition to allowing the installation of the equipment with modernized machinery, the manufacturing processes will be automated. The objectives that allow the execution of the project are the compilation of the technical information that support the parameters of basic design and the appropriate characteristics that the device must have, the sizing of the system by the mathematical calculation and the implementation of the electronic equipment that allow the CNC control. The research is the applied type. That is, scientific information from books, scientific articles, websites and catalogs of manufacturers that support the technical argumentation; For its subsequent application in the design and construction of a CNC machining machine by laser. The results obtained are the cutting power of a 40 W CO2 laser in a 20 * 30 cm work area.